Label-Free Non-linear Multimodal Optical Microscopy—Basics, Development, and Applications - Mazumder, Nirmal; Balla, Naveen K.; Zhuo, Guan-Yu; Kistenev, Yury V.; Kumar, Rajesh; Kao, Fu-Jen; Brasselet, Sophie; Nikolaev, Viktor V.; Krivova, Natalya A. (Frontiers in Physics, 2019)
Nonlinear optical (NLO) microscopy has proven to be a powerful tool especially for tissue imaging with sub-cellular resolution, high penetration depth, endogenous contrast specificity, pinhole-less optical sectioning capability. In this review, we discuss label-free nonlinear optical microscopes including the two-photon fluorescence (TPF), fluorescence lifetime imaging microscopy (FLIM), polarization-resolved second harmonic generation (SHG) and coherent anti-Stokes Raman scattering (CARS) techniques with various samples. The nonlinear signals are generated from collagen in tissue (SHG), amylopectin from starch granules (SHG), sarcomere structure of fresh muscle (SHG), elastin in skin (TPF), nicotinamide adenine dinucleotide (NADH) in cells (TPF) and lipid droplets in cells (CARS). Again, the nonlinear signals are very specific to the molecular structure of the sample and its relative orientation to the polarization of the incident light. Thus, polarization-resolved nonlinear optical microscopy provides high image contrast and quantitative estimate of sample orientation. An overview of the advancements on polarization-resolved SHG microscopy including Stokes vector based polarimetry, circular dichroism, and susceptibility are also presented in this review article. The working principles and corresponding implements of above-mentioned microscopy techniques are elucidated. The potential of time-resolved TPF lifetime imaging microscopy (TP-FLIM) is explored by imaging endogenous fluorescence of NAD(P)H, a key coenzyme in cellular metabolic processes. We also discuss single laser source time-resolved multimodal CARS-FLIM microscopy using time-correlated single-photon counting (TCSPC) in combination with continuum generation from photonic crystal fiber (PCF). Using examples, we demonstrate that the multimodal NLO microscopy is a powerful tool to assess the molecular specificity with high resolution.